Anisotropy effects in diamond under nanoindentation. (June 2018) - Huang, Cheng; Peng, Xianghe; Yang, Bo; Xiang, Henggao; Sun, Sha; Chen, Xiang; Li, Qibin; Yin, Deqiang; Fu, Tao
Abstract: We performed molecular dynamics simulations for the nanoindentation on (001), (110) and (111) surfaces of a single crystal diamond (SCD) to investigate the orientation-dependence of its mechanical behavior. We found that the elastic and plastic behavior of SCD, such as Young's modulus, critical pressure and hardness, depend strongly on the orientation of the indented surface because of the anisotropic nature of SCD. The load drop events in the P – h curves were observed, which corresponds to a transition from elastic to plastic deformation. The stress distributions induced by indentations on differently oriented surfaces are very different, so are the evolutions and distributions of the dislocations, though it was found that in all the three cases the initial plasticity could be attributed to the nucleation and growth of 1/2<110>{111} perfect dislocation loops, which is consistent with the experimental results and the prediction by the stacking fault energy. It shows that the dislocation distributions exhibit dual-, triple- and four-fold rotation symmetries in the cases of (110), (111) and (001), respectively. The effects of indenter size ( R ) and speed ( v ) were also investigated, which show that R and v strongly affect the response of SCD and also verify of the simulated results. Graphical abstract: Image 1